Impacts of peat fire on soil flora and fauna, soil properties and environmental damage in Riau Province, Indonesia - BASUKI WASIS; BAMBANG HERO SAHARJO; ERIANTO INDRA PUTRA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Wasis B, Saharjo BH, Putra EI. 2019. Impacts of peat fire on soil flora and fauna, soil properties and environmental damage in Riau Province, Indonesia. Biodiversitas 20: 1770-1775. Land fires set by communities can result in the death of flora and fauna, damage the soil, and cause smoke disasters. In this study, we focused on the burnt community land in Riau Province, where we conducted a soil analysis through purposive sampling to highlight the effect of the fires on the environment. Our findings showed that fires caused a decrease of peat soil thickness of 10-15 cm, and resulted in 100% mortality of soil flora and fauna. We found a significant increase in the Ca and soil pH after a fire, but total microorganisms, total fungi, and soil respiration are found decreased. Our results strongly showed that the soil and environmental damage of burnt peat soil on community land exceeded the minimum criteria to be classified as "environmental damage" as defined by Indonesian Government Regulation No. 4/2001 (PP No 4/2001) for the parameters of bulk density, porosity, pH, organic C, N, total microorganisms, total fungi, and respiration.